PENGARUH FULL DAY SCHOOL DAN SERTIFIKASI GURU TERHADAP KINERJA GURU - Utari, Ade Silvia; Tobari, Tobari; Puspita, Yenny (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2020)
This study determined the effect of Full Day School and Teacher Certification on Teacher Performance. Data in this study were collected through distributing questionnaires to respondents. The results of filling out the questionnaire were analyzed by multiple regression analysis through t test, F test, and the coefficient of determination test. The population of the study was junior high school teachers in Sukarami Subdistrict from 4 schools totaling 109 people. The sample is based on calculations using the Slovin formula. 86 teachers were obtained as a sample. The results of this study (1) There is an effect of Full Day School on the Performance of Junior High School Teachers in Sukarami District; (2) There is an effect of teacher certification on teacher performance; (3) There is the influence of Full Day School and Teacher Certification together on the performance of junior high school teachers in Sukarami District. Based on the test results of the coefficient of determination, the teacher performance variable is influenced by the full day school variable and teacher certification. Besides that it is influenced by other factors outside the research variables.